Directions of spiritual and educational activity - Rakhimov Asomiddin Anorboevich (International Consortium of Education and Culture Research Studies, 2020)
This article highlights the role of spiritual and educational activity in the context of education reform requirements and its role in human development. It also describes the main tasks and directions of spiritual and educational activities